Factor the following:
15 x y - 45 x - 6 y + 18
Factor 3 out of 15 x y - 45 x - 6 y + 18:
3 (5 x y - 15 x - 2 y + 6)
Factor terms by grouping. 5 x y - 15 x - 2 y + 6 = (5 x y - 2 y) + (6 - 15 x) = y (5 x - 2) - 3 (5 x - 2):
3 y (5 x - 2) - 3 (5 x - 2)
Factor 5 x - 2 from y (5 x - 2) - 3 (5 x - 2):
Answer: 3 (5 x - 2) (y - 3)
Answer:
=3x³+2x²−27x−18
Step-by-step explanation:
(x+3)(x−3)(3x+2)
=((x+3)(x−3))(3x+2)
=((x+3)(x−3))(3x)+((x+3)(x−3))(2)
=3x³−27x+2x²−18
=3x³+2x²−27x−18
Answer:
1. (4,5)
The average rate of change of f(x) remain constant (4). Over the interval (4,5), g(x)=5,2 exceeding the change of f(x).
2. None!! REMAIN CONSTANT AND INCREASE.
The rate of change of f(x) remain constant (4) and g(x) increases.
3. g(x) exceeds the value of f(x)
F(X)=31 < G(X)=35,7
4. EVENTUALLY.
Answer:
A.) 0.33
Step-by-step explanation: